Cloud Computing Revisited For E-Learning Systems with Some Improvements with Auditing - Burney, S. M. Aqil; Alam, Fawad; Burney, Shamaila (Discoveries in Agriculture and Food Sciences, 2022)
E-learning has brought great dynamics and parameters in the field of education and research. It has revolutionized the way learning has imparted to students. The perks of e-learning include consistency, scalability, cost cut down, in contrast to the traditional learning method. It is equally well-being and doing great in every field of learning. During this period of COvid-19 e-learning is developing and has completely taken over and administrated the education system. But along with the advancement of the field there comes the challenges. One would always keen to look up for the technology to make the learning process reliable, faster, easier to use, and can enhance with more interactive features. This is the spot where cloud computing stands with a bunch of its unmatchable capabilities. Cloud Computing refers to provide the computing assets on the internet which may include storage, servers, software systems, databases, online management systems, and online applications. Having a paradigm like Cloud Computing gives an edge for innovators and entrepreneurs to design and develop their mainstream projects and products with ease. This paper provides an insight into how Cloud Computing has the potential and can be the primary driver of e-learning. How the field of e-learning can benefit from this revolutionary technology. This research discusses the cloud services, architecture nature as a service for the e-learning environment. Further, the comprehensive converses about the impact of Cloud Computing on e-learning along with the security fears and features can potentially get the most out of the combination of both fields with the introduction of auditing of the system .